Recent Development of Active Ingredients in Mouthwashes and Toothpastes for Periodontal Diseases - Meenakshi Rajendiran; Harsh M Trivedi; Dandan Chen; Praveen Gajendrareddy; Lin Chen (Molecules, 2021)
Periodontal diseases like gingivitis and periodontitis are primarily caused by dental plaque. Several antiplaque and anti-microbial agents have been successfully incorporated into toothpastes and mouthwashes to control plaque biofilms and to prevent and treat gingivitis and periodontitis. The aim of this article was to review recent developments in the antiplaque, anti-gingivitis, and anti-periodontitis properties of some common compounds in toothpastes and mouthwashes by evaluating basic and clinical studies, especially the ones published in the past five years. The common active ingredients in toothpastes and mouthwashes included in this review are chlorhexidine, cetylpyridinium chloride, sodium fluoride, stannous fluoride, stannous chloride, zinc oxide, zinc chloride, and two herbs—licorice and curcumin. We believe this comprehensive review will provide useful up-to-date information for dental care professionals and the general public regarding the major oral care products on the market that are in daily use.